1997
DOI: 10.1017/s1357729800008663
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environment on behavioural activity, ACTH, (β-endorphin and cortisol in pre-farrowing gilts

Abstract: This study examined the temporal relationships between behavioural activity and hormones associated with stress in gilts farrowing in two environments. Thirty-one Large White × Landrace gilts with indwelling jugular catheters were blood sampled daily (08.00 and 16.00 h) from 10 days before their expected parturition date (EPD). Five days before EPD they were moved to either a farrowing crate (C) with no bedding, or a pen (P) (2·5 m × 3·0 m) with straw provided and were blood sampled daily at 08.00, 12.00 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 21 publications
4
31
1
Order By: Relevance
“…There was a difference between treatments in available space for the sow, and as results by Lawrence et al (1994) and Jarvis et al (1997) indicated that the close confinement of the crate Values within a row without a common superscript differ (P , 0.05). *P , 0.05; **P , 0.01; ***P , 0.001.…”
Section: Stillbirthsmentioning
confidence: 97%
“…There was a difference between treatments in available space for the sow, and as results by Lawrence et al (1994) and Jarvis et al (1997) indicated that the close confinement of the crate Values within a row without a common superscript differ (P , 0.05). *P , 0.05; **P , 0.01; ***P , 0.001.…”
Section: Stillbirthsmentioning
confidence: 97%
“…Compared to loose-housing, these systems require also less space and are easier to manage, that is handling of animals and manure removal (Blackshaw et al, 1994;Barnett et al, 2001;Baxter et al, 2012;Hales et al, 2013). Nevertheless, crates are currently under discussion because the movement of the sows, and thus the natural animal behaviour and welfare are highly impaired (Lawrence et al, 1994;Jarvis et al, 1997). As a consequence, in countries like Norway, Sweden or Switzerland farrowing crates are already forbidden by law.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the inadequacy of nest-building behaviour in crated environments may influence the duration of farrowing and therefore the incidence of stillbirths. The lack of space and substrate when sows are kept in standard farrowing crates precludes feedback from nest-building behaviour and has been shown to constitute a stress for the sow (Lawrence et al, 1994;Jarvis et al, 1997 andDamm et al, 2003). Further work dissociating the effects of space and substrate demonstrated that space restriction per se induced elevated hypothalamic pituitary adrenal (HPA) activity which is deemed indicative of physiological stress .…”
Section: Introductionmentioning
confidence: 99%